Conceptual frame of water conflicts in the Mediterranean - Shatanawi M.; Shammout M.; Naber S.; Aboul-Fotoh N.Z.; Eddin Abdin A.; Sedky S.; Candela L.; Domingo F.; Berbel J.; Alarcón J.J.; Laureano P.; Tamoh K.; et al. (Water culture and water conflict in the Mediterranean area, 2008)
The conceptual frame of water conflict is based on research papers presented at the first workshop of the MELIA (MEditerranean DiaLogue on Integrated Water ManAgement) project. The papers have reported some of the main causes of water conflict in cases located in Spain, Egypt, Jordan and Italy. These causes are concentrated in the following : climate and water distribution, water use and demand, rapid development in the irrigation projects, over/lap/ lack of responsibilities, insufficient maintenance, inadequate finance, poor management, lack of law enforcement and of awareness. Water conflict can be mitigated based on water transfer, policy strategy and action plans, better management of existing water resources, development of hydrological plan, environmental considerations and cost-benefit analysis, awareness in field of water, ancient water techniques for security and sustainable future.
1. MELIA Workshop Water Culture and Water Conflict, 2007/11/22-25, Nabeul-Médenine (Tunisia)